SYUBHAT ‎ ‎(Allah Tidak Menjamin Terpeliharanya Hadis Dari Pemalsuan‎ Sebagaimana Jaminannya Terhadap Alquran)‎ - Muhammad Rois (Al-Thiqah: Journal of Hadith and Prophetic Tradition, 2024)
The phenomenon of the emergence of Sunnah denial has not stopped, even though experts have refuted, criticized, and answered the arguments built by Sunnah-denying groups. In Indonesia, one of the founding figures of the Sunnah sect named Mochammad Ihram Sutarto, who is based in Jakarta, combed the younger generation with minimal religious knowledge. In the Middle East, the phenomenon of rejecting the modern Sunnah is allegedly rooted in India. Ahmad Khan was the founder of the Sunnah-defiant group in the nineteenth century. Ahmad Ṣubhi Mansūr is an educator at Al-Azhar University who brought modern Sunnah denial of thought in Egypt. This group calls their name as Ahl AlQuran. This Sunnah-defiant group also spread its ideology to Syria. Therefore, Muslim scholars refute the Sunnah inkar. Dalam penelitian ini, pertama penulis menggunakan metode analisis wacana kritis. The analysis method can be said to be a continuation of a research with the initial analysis informing the data that is then collected. Based on the results of the data collected, it can be concluded that the sunnah inkar in the time of the Prophet has not been found, but the information about the sunnah inkar has been said by the Prophet in a hadith narrated by Abū Dawud. As for the next stage, the inkar sunnah can be classified into two, between the classical sunnah denial and the modern sunnah denial. The rejection of the classical sunnah was rampant during the time of al-Syafi''i with the emergence of groups that rejected the authority of the sunnah as the source of Islamic law. Meanwhile, this sunnah rejection movement appeared in modern times (twentieth century) in India